Effectiveness of Verticillium lecanii against the parasitic stage of the tick Boophilus microplus (Acari: Metastigmata: Ixodidae) - RIJO-CAMACHO, ESPERANZA; NAVARO, GILBERTO; RODRÍGUEZ, REGLA MARÍA; MURILLO, ENA YABER (Revista Colombiana de Entomología, 1998)
The present work was carried out in 1990 at the cattle breeding enterprise El Cangre, Havana province where the effectiveness of the fungus Verticillium lecanii (Zimn) Viegas LBVI-2 strain was determined against the parasitic stages of Boophilus microplus (Canestrini, 1887). The experiments were made by spraying the biological product on cattle, one of them with yarded animals and the other one in grazing areas, the latter having been compared with cattle treated with a mixture of clorfenvinphos plus cimiazol. The biopreparation showed since the first treatment applied to the stabled animals, effectiveness which varied between 47.5 and 78.7%. In the fourth bath, the regulation of the ectoparasite was between 93.5 and 98.7%, after which it was not anymore necessary to treat further. The effectiveness of the biological product sprayed on animals in grazing areas did not significantly differ from that obtained by spraying chemical acaricides.